Communication Strategies Used by Students in Indonesia - Whandani Anasan Arum; Wahyu Taufiq (International Consortium of Education and Culture Research Studies, 2019)
This research aims at investigating the communication strategies used by the students at some courses in Indonesia. The data is taken from conversations and interview five students in active speaking class. The data were used observed and recorded. After obtaining the data from the dialogue script of the students, the researcher concluded that their communication strategies were very relevant with Tarone's theory. In this theory explained that the communication strategy has two types; verbal and non verbal. Verbal communication strategie,s there are several kinds, such as; Avoidance (topic message, avoidance abandonment), Paraphrase (approximation, word coinage, circumlocution), Borrowing (literal translation, language mix), and the Appeal of Assistance. While the non verbal communication strategy, this is only one category which is Mime, when the student uses non verbal tactics in place of lexical item or action. Effect of the study in this writing form is expected to be an important source of information for teachers and learners because the purpose is to increase education quality, especially related to the problem of mastering speaking and using the communication strategies.